Disseminated Tuberculosis Mimicking Ankylosing Spondylitis - Valérie Huyge; Serge Goldman; Muhammad S. Soyfoo (Case Reports in Rheumatology)
Ankylosing spondylitis is a chronic inflammatory disorder affecting mainly the axial skeleton. Here we report a case of a man with a clinical suspicion of ankylosing spondylitis but with a persistence of increased inflammatory markers. In this case, 18F-FDG-PET/CT revealed multiple hypermetabolic lesions in axial skeleton, lymph nodes, and the lung, suggestive of either disseminated tuberculosis or lymphoma. Histological analysis of the pulmonary lesion revealed mycobacterium tuberculosis. This case highlights, firstly, the importance of excluding other diagnoses in the presence of clinical picture of ankylosing spondylitis and high inflammatory markers and, secondly, the determining role of PET/CT.